2011
DOI: 10.1007/s11207-011-9728-3
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of the Ionospheric Behavior During the Solar Cycle 23 – 24 Minimum

Abstract: The Solar Cycle 23 -24 minimum has been considered unusually deep and complex. In this article we study the ionospheric behavior during this minimum, and we have found that, although observable, the ionosphere response is minor and marginally exceeds the range of normal geophysical variability of the system. Two main ionospheric parameters have been studied: vertical TEC (vTEC, total electron content) and NmF2 (peak concentration of the F region). While vTEC showed a consistent modest decrease of the mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
(22 reference statements)
2
54
0
Order By: Relevance
“…Quantitative analysis indicates that solar EUV irradiance, as the primary contributor to the ionization, created a record low ionospheric electron density during the cycle 23/24 minimum. Both the space-borne measurements of EUV irradiance and the proxy 10.7 cm solar radio flux (F10.7 index) in this period were found to be lower than other recent minima, and accordingly the ionospheric critical frequency foF2 and total electron content (TEC) shrank to a record low level (Liu et al, 2011a;Araujo-Pradere et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…Quantitative analysis indicates that solar EUV irradiance, as the primary contributor to the ionization, created a record low ionospheric electron density during the cycle 23/24 minimum. Both the space-borne measurements of EUV irradiance and the proxy 10.7 cm solar radio flux (F10.7 index) in this period were found to be lower than other recent minima, and accordingly the ionospheric critical frequency foF2 and total electron content (TEC) shrank to a record low level (Liu et al, 2011a;Araujo-Pradere et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…The ionospheric response to the weak CIRs was marginal but observable (Araujo-Pradere et al 2011). However, the weak recurrent geomagnetic activity due to CIRs did produce distinct variability in the thermospheric density at an altitude of 400 km above ground (Lei et al 2011 and references therein).…”
Section: Effect Of the Weak Solar Activitymentioning
confidence: 98%
“…Solomon et al (2010) suggested that this was consistent with the observed EUV irradiance decrease, including a 15% decrease from 1996 to 2009 in the He 304 Å emission observed by the SOHO Solar Extreme-ultraviolet Monitor (SEM). Araujo-Pradere et al (2011) looked at NmF2 and the vertical total electron content (vTEC) at several mid-latitude locations for summer and winter months between 1996 -1997 and 2007 -2009 to see if there was a similar decrease between the WSM solar minimum (1996) and WHI solar minimum. The results were inconclusive for NmF2, but vTEC values did show a decrease of the total electron content in the ionosphere and plasmasphere from the ground to 20 000 km (the altitude of all global positioning satellites) between 1996 and 2008, especially in early evening hours.…”
Section: The Response At Geospacementioning
confidence: 99%
“…Woods et al, 2009;Solomon et al, 2010Solomon et al, , 2011Araujo-Pradere et al, 2011;Emery et al, 2011;Gibson et al, 2011;Haberreiter, 2011;Lei et al, 2011;Wang et al, 2011;White et al, 2011) • Cosmic-ray modulation? Jian, Russell, and Luhmann, 2011) • Morphology of heliosphere?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation